Analisis Maslahah Dalam Relasi Pasangan Disabilitas Intelektual untuk Mewujudkan Keluarga Sakinah (Studi Kasus Pada Perkawinan Tunagrahita Di Kabupaten Ponorogo) - Sakdiyah, Ela Munifatus (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2024)
In Sidoharjo Village, Jambon District, as well as in Karangpatihan Village and Pandak Village, Balong District, Ponorogo Regency, several residents experience intellectual disabilities or tunagrahita. This phenomenon of mass tunagrahita has been occurring for decades, and some individuals with intellectual disabilities have also entered into marriages. The marriages among individuals with intellectual disabilities in Ponorogo Regency arise from concerns of families and the community about the possibility of zina (adultery). Although individuals with intellectual disabilities may have mental challenges, they still possess sexual instincts similar to those of normal individuals. However, marriage is not merely a means to legitimize sexual relations. The research method used is qualitative with a case study approach, aiming to investigate the phenomenon in the real-life context of three villages where many residents experience tunagrahita and have married. This study aims to describe the concept of spousal relationships, the ways in which tunagrahita couples meet family needs, and the child-rearing methods applied by tunagrahita couples in forming a sakinah family. Additionally, this research analyzes the implementation of spousal relationships among tunagrahita couples in creating a sakinah family from the perspective of Al-Buthi's maslahah. The findings indicate that spousal relationships function well despite their communication limitations; they can meet their needs through independent work and empowerment, and they can effectively raise their children with the support of family and community. The happiness and harmony of the family are evident in how they live their lives without significant conflicts. This suggests that their marriages reflect a maslahah both for the tunagrahita couples and their families, consistent with Al-Buthi's theory of maslahah. Keywords: intellectual disability, sakinah, maslahah, tunagrahita